Precautions taken by airlines during the pandemic and customer relationship management (CRM): The example of the Covid-19 pandemic - Mezde, Ayça; Ertek, Ahmet; Ertek, Serap (Zenodo, 2024)
Infectious diseases can easily spread to other regions through travel with the development of air transportation. For example, the coronavirus, which was first seen in Wuhan, China, in 2019, spread rapidly all over the world, and governments took measures to restrict travel. Airline companies suddenly stopped their operations with the "restrictions on air travel" decision included in the World Health Organization recommendations and were greatly affected by this process. During this process, customer relationship management gained more importance compared to normal periods. In this context, the customer relationship management applied in airline companies during the epidemic period in question was examined with the descriptive analysis technique by preferring the qualitative research method. The Covid-19 pandemic was taken as a sample in the study, and the implemented practices were presented. It is thought that this study will be beneficial to businesses in the event of a possible epidemic with the occurrence of different infectious diseases such as MPOX disease, avian influenza A(H9N2) virus, Chandipura vesiculovirus (CHPV) infection, and Oropouche virus (OROV) seen in 2024. In the study, the measures taken by airline companies during the Covid-19 pandemic process experienced by the aviation sector were presented to the reader, and it was concluded that airline companies that managed this process well in 2024 achieved successful results in customer satisfaction.